Calculation of Radioactive Source Term Release from Flexblue SMR - Setiawan, M. Budi; Udiyani, Pande Made (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2021)
One of the National Research Programs (PRN) in the energy sector of the Indonesian Ministry of Research and Technology for the period of 2020-2024 is the assessment of small modular reactor (SMR) nuclear power plant (NPP). French-designed Flexblue is a PWR-based submerged SMR with a power of 160 MWe. The Flexblue reactor module was built on the ocean site and easily provided the supply of reactor modules, in accordance with the conditions of Indonesia as an archipelagic country. As a part of safety aspect, it is necessary to know the release of fission products (source term), for the study of the radiation safety of a nuclear reactor. This paper aims to examine the source term in normal and abnormal operating conditions, as well as postulated accidents. Based on the Flexblue reactor core parameter data, the calculation of the reactor core inventory using the ORIGEN2 software is evaluated. The source term calculation uses mechanistic and graded approach. The normal source term is calculated assuming the presence of impurities on the fuel plate, due to fabrication limitations. Meanwhile, the abnormal source term is postulated in the LOCA event. The highest source term activity of Flexblue both under normal and abnormal conditions is that of the noble gas group radionuclides. In the normal operation, the maximum source term is 2.14E+04 Ci. In the small-LOCA event, the maximum source term activity is 4.86E+03 Ci, while the maximum activity of the source term under large-LOCA event is 9.73E+05 Ci.